FAKTOR YANG MEMPENGARUHI SENTIMEN PUBLIK TERHADAP KEBIJAKAN WOLBACHIA-AEDES - Budiyanti, Rani; Kusariana, Nissa (Jurnal Kesehatan Manarang, 2025)
Dengue fever represents a significant public health challenge in Indonesia. The Wolbachia-Aedes mosquito policy innovation, designed to impede dengue virus transmission, has been implemented in various urban areas as an effective control strategy. Nevertheless, public acceptance has emerged as a crucial determinant of the policy's successful implementation. This study seeks to examine public perceptions and sentiments concerning the Wolbachia-Aedes policy implementation. A quantitative approach with a cross-sectional design was employed in this study. A total of 110 respondents were selected through cluster sampling in Tembalang, Semarang City, Indonesia. Data collection was conducted via interviews utilizing a structured questionnaire. Findings indicate that 53.6% of respondents held a positive perception of the policy. This perception was significantly influenced by factors related to knowledge and information access (p<0.05). However, the majority of respondents underscored the necessity for enhanced dissemination and improved education regarding the Wolbachia-Aedes policy. Future research should investigate the potential adverse impacts of the Wolbachia-Aedes policy and provide more comprehensive scientific evidence. Additionally, intensive risk communication and outreach are imperative to cultivate greater community support for the policy's implementation.